ANALISIS PENTINGNYA BIMBINGAN KONSELING TERHADAP ANAK SEKOLAH DASAR DI SD / MI MUHAMMADIYAH 5 SURABAYA - Hida Septina Syaikha; Anita Tri Wahyuni; Firda Aisyah Yulia Rachman (Universitas Muhammadiyah Surabaya, 2022)
This study aims to determine the importance of counseling guidance for children in elementary schools. Students are individuals who really need guidance to achieve the desires, interests, talents, ideals and personalities in the formation of attitudes and morals. Guidance can direct children to their academic, emotional, interests, talents and social aspects. Guidance and Counseling is a service providing assistance provided by counselors to students, so that students can understand themselves, make decisions, understand their own potential, know how to develop their potential, and have the nature of responsibility for the decisions they make.Â Keywords: Guidance; Counseling; Students